THE IMPORTANCE OF DIGITAL TRANSFORMATION IN THE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
The article substantiates the need for digital transformation of management processes in higher education institutions. The relevance of digital management, state policy, theoretical approaches, foreign experience and the situation in Uzbekistan are highli ghted, the advantages of digitalization and conclusions are drawn.
Keywords: digital management; higher education; digital transformation; distance learning; HEMIS; digital economy; information system; educational innovation